Psoriasis improvements and inflammatory biomarker normalization with secukinumab: the randomized ObePso-S study. Issue 1 (January 2023) - Blauvelt, Andrew; Pariser, David M.; Tyring, Stephen; Bagel, Jerry; Alexis, Andrew F.; Soung, Jennifer; Armstrong, April W.; Muscianisi, Elisa; Kianifard, Farid; Steadman, Jennifer; Sarkar, Rajendra Prasad; Garcet, Sandra; et al.
Abstract: Background: The IL-17A inhibitor secukinumab has demonstrated consistent efficacy and safety in patients with moderate-to-severe plaque psoriasis, with normalization of molecular and histopathologic psoriasis markers. Objective: To investigate treatment effects of secukinumab on clinical signs and psoriatic inflammation markers over 52 weeks in patients with psoriasis. Methods: In the ObePso-S study (NCT03055494), patients with psoriasis were randomized 2:1 to receive secukinumab 300 mg (n = 54) or placebo (n = 28), stratified by body weight (<90 or ≥90 kg), for 52 weeks. At Week 12, patients receiving placebo were switched to secukinumab. Psoriasis Area and Severity Index improvement of 90% (PASI90) and Investigator's Global Assessment modified 2011 0/1 responses were assessed at Weeks 12 and 52. Immunohistochemistry for keratin 16 (K16) and gene expression profiles were evaluated in lesional and non-lesional skin biopsies collected at baseline, Week 12, and Week 52. Results: Of patients receiving secukinumab, 55.8% and 59.6% achieved PASI90 at Weeks 12 and 52, respectively. K16 was absent in 93.1% of Week 12 PASI90 responders and 93.6% of Week 52 PASI90 responders, which mirrored the down-regulated expression of psoriatic inflammation. Week 52 PASI90 non-responders experienced regression of clinical and inflammatory marker responses toward baseline levels. Lower control of inflammatory gene expression at Week 12 was associated with suboptimal clinical responses at Week 52. Conclusion: Sustained clinical responses with secukinumab were associated with rapid and sustained normalization of K16 and inflammatory gene expression in most patients. Molecular anti-inflammatory effects of secukinumab at Week 12 were associated with clinical responses at Week 52. Highlights: Secukinumab reduced the severity of psoriasis and promoted histologic reversal of psoriasiform hyperplasia at Week 12. These responses were maintained through Week 52 in most patients. Patients who attained Week 52 PASI90 responses had improvement in psoriasis-associated gene expression as early as Week 12. Patients who had suboptimal cellular and molecular responses at Week 12 failed to achieve PASI90 at Week 52. Increasing levels of disease control at Week 52 were associated with increased improvements in inflammatory gene expression.